2018
DOI: 10.33394/jollt.v6i1.809
|View full text |Cite
|
Sign up to set email alerts
|

Reading Interest of Senior High School Students: A Case Study

Abstract: Nowadays, the development of the teaching and learning of English as a foreign language has been transformed. Learners do not only focus on the learning of speaking and writing but also reading since they are required to be able to smartly respond to the texts they are reading. The development of the information and technology forces the focus of teaching and learning on the critical reading that might be less interesting for the students. The students may not know their interest in reading before they start r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 2 publications
0
7
0
4
Order By: Relevance
“…On the other hand, several studies showed many EFL learners have a low interest in reading. One of them is the study conducted by Rachmawati (2018). Her study reported the EFL learners did the reading activity when they are in learning processes and when they are in examination (for answering the question) (Rachmawati, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several studies showed many EFL learners have a low interest in reading. One of them is the study conducted by Rachmawati (2018). Her study reported the EFL learners did the reading activity when they are in learning processes and when they are in examination (for answering the question) (Rachmawati, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Two factors influence the students' motivation based on a study conducted by Almekhlafy & Alqahtani (2020); motivated by themselves (intrinsic motivation) and motivated from outside (extrinsic motivation) (Almekhlafy & Alqahtani, 2020). These factors (intrinsic and extrinsic) can build the students" interest in reading (Rachmawati, 2018).…”
Section: The Process Of Reading and Reading Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, readers interact dynamically with the text as they try to elicit the meaning. Reading is classified as recognition of printed or written symbols, which serve as stimuli for the recall of meanings built up through the reader's past experience (Rachmawati, 2018). It has also been described as a process of translating alphabetical symbols into a form of language from which the native speaker has already derived the meaning (Bond, 1984: 02).…”
Section: Introductionmentioning
confidence: 99%
“…Terlebih anak-anak sebagai generasi penerus harus memiliki wawasan yang luas. Salah satu cara untuk memperoleh pengetahuan yang luas yaitu dengan banyak membaca (Rachmawati, 2018). Karena keterampilan membaca diperlukan untuk kepentingan pemenuhan kebutuhan mendapatkan informasi secara holistik dari apa yang dibaca, saran refleksi, dan kepentingan studi sesuai ruang lingkup disiplin keilmuan (Siti Anisatun Nafi'ah,2018:39).…”
unclassified